Dopamine: Agonists and Neurodegenerative Disorders - Khanam, Saba; Siddique, Yasir H. (Current Drug Targets, 2018)
Background: Parkinson's disease (PD) is a neurodegenerative disease characterized by the loss of dopaminergic neurons within the substantia nigra pars compacta (SNpc). Despite many researches, there is still no cure for this disease. Levodopa is the first line treatment of PD, but the long term use of it leads to motor impairments and dyskinesias. The dopamine agonists are the preferred choice for the treatment of PD. They are neuroprotective in nature but have side effects. Objective: Our aim was to review the work that has been carried out on dopamine agonists and the future possibilities to reduce their side effects. Conclusion: In this review, we highlighted the metabolism of dopamine, different types of dopamine agonists with their properties and possible side effects.
Keywords: neurotransmitters